Efektivitas Penggunaan Artificial Intelligence (AI) Terhadap Critical Thingking Peserta Didik di SMK Negeri 33 Jakarta - Syabrina Fajriannisa; Nadiah; Maria Ulfah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
This research is motivated by the results of observations conducted by researchers on students at SMK Negeri 33 Jakarta. The problem in this study is based on the phenomenon of low critical thinking skills of students and the increasing use of Artificial Intelligence (AI) technology, especially platforms such as ChatGPT, in learning activities. Although Artificial Intelligence (AI) provides convenience in learning, there are concerns about the emergence of technological dependency that can reduce students' independent and analytical thinking skills. This study aims to determine the effectiveness of the use of Artificial Intelligence (AI) on critical thinking skills. The research method used is a quantitative method with a survey approach involving students from class X Hospitality 2. Data collection techniques were carried out through questionnaires, observation, documentation, and interviews. The research sample consisted of 37 students of SMK Negeri 33 Jakarta who were selected using a simple random sampling technique. The results of the study show that when viewed from the Product Moment coefficient test, it produces "rxy" or "ro" of 0.641. While "rt" in the 5% significance table = 0.329 and a significance level of 1% = 0.424. Thus, it can be seen that "ro" > "rt" both at 5% and 1% significance. Therefore, based on these results, the Alternative Hypothesis (Ha) is accepted or approved and the Null Hypothesis (Ho) is rejected or not approved. Based on this study, it can be concluded that there is an influence of the use of Artificial Intelligence (AI) on Critical Thinking of Students at SMK Negeri 33 Jakarta. Keywords: Artificial Intelligence (AI), Critical Thinking, Students.